Non-LTE model calculations for SN 1987A and the extragalactic distance scale - Schmutz, W.; Abbott, D. C.; Russell, R. S.; Hamann, W.-R.; Wessolowski, U. (The Astrophysical journal, 1990)
This paper presents model atmospheres for the first week of SN 1987A, based on the luminosity and density/velocity structure from hydrodynamic models of Woosley (1988). The models account for line blanketing, expansion, sphericity, and departures from LTE in hydrogen and helium and differ from previously published efforts because they represent ab initio calculations, i.e., they contain essentially no free parameters. The formation of the UV spectrum is dominated by the effects of line blanketing. In the absorption troughs, the Balmer line profiles were fit well by these models, but the observed emissions are significantly stronger than predicted, perhaps due to clumping. The generally good agreement between the present synthetic spectra and observations provides independent support for the overall accuracy of the hydrodynamic models of Woosley. The question of the accuracy of the Baade-Wesselink method is addressed in a detailed discussion of its approximations. While the application of the standard method produces a distance within an uncertainty of 20 percent in the case of SN 1987A, systematic errors up to a factor of 2 are possible, particularly if the precursor was a red supergiant.